2019
DOI: 10.1002/adma.201905060
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Doping Mottronics in Strongly Correlated Perovskite

Abstract: Hydrogen (proton) induced switchable multiphase transformations in d-band electron-correlated materials recently opened a new field for exploring merging multifunctional proton-gated electronic devices, [1] synaptic plasticity, [2,3] sensors, [4] and novel energy conversion devices. [5] Compared to other dopant elements, hydrogen is small in radius and has high ionic mobility. [1,[4][5][6] Therefore, the proton distribution is highly adjustable via external electric fields, and the respective tuning of the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 40 publications
1
38
0
2
Order By: Relevance
“…Rare earth nickelates with a perovskite structure (ABO 3 ) are of broad research interest due to their highly sensitive electronic phase diagram with respect to orbital electron occupancy. As a representative, NdNiO 3 (NNO) shows metallic conduction behavior and is neutral gray at room temperature with single electron occupancy in the e g orbital of Ni 3d bands (e g 1 ). Upon cation intercalation accompanied by an extra electron filling, the Ni state in the pristine NNO experiences crossover to the Ni 2+ state that is highly localized (e g 2 ). , The strong carrier localization opens up an optical gap and makes the material transmissive. The ion–electron intercalation therefore leads to completely opposing effects compared with WO 3 , as shown schematically in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth nickelates with a perovskite structure (ABO 3 ) are of broad research interest due to their highly sensitive electronic phase diagram with respect to orbital electron occupancy. As a representative, NdNiO 3 (NNO) shows metallic conduction behavior and is neutral gray at room temperature with single electron occupancy in the e g orbital of Ni 3d bands (e g 1 ). Upon cation intercalation accompanied by an extra electron filling, the Ni state in the pristine NNO experiences crossover to the Ni 2+ state that is highly localized (e g 2 ). , The strong carrier localization opens up an optical gap and makes the material transmissive. The ion–electron intercalation therefore leads to completely opposing effects compared with WO 3 , as shown schematically in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite magnetic materials have been studied for almost 50 years. These systems offer a degree of chemical flexibility which allows the relation between the oxides structure, and electronic and magnetic properties that can be controlled in various ways, such as: Doping [61][62][63], magnetic field [64][65][66], electric field [67,68], temperature [69][70][71], pressure, and photoexcitation [72][73][74][75]. Research on these compounds has revealed the relevant phe-nomenon of magnetoresistance [76][77][78][79], and has led to the formulation of important physical concepts such as double exchange [1] and the Jahn-Teller polaron [80].…”
Section: Perovskite Compounds: General Concepts and Applicative Indicmentioning
confidence: 99%
“…However, the switching speed of an insertion transistor is fundamentally limited by the slow rates at which ions are inserted into and extracted from the VO 2 lattice. [ 1,3,6 ] To overcome the slow switching by H + insertion, in the previous study, the rate of proton‐induced phase transformation was controlled by inducing planar defects that determine alignment [ 16 ] and density, [ 17 ] but these strategies could only be achieved within a narrow range of a control parameter (e.g., use of a specific substrate). Moreover, externally inserted H + dynamics under electric field enable to be modulated by the amount of intrinsically‐formed oxygen ionic defects (e.g., oxygen vacancies), which have a higher activation barrier for migration than H + do, [ 18 ] but the influence of oxygen defects in the lattices on the rate of H + insertion/extraction by electric field has yet to be explored.…”
Section: Figurementioning
confidence: 99%